2013
DOI: 10.1167/iovs.13-12551
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Signatures in Tree Shrew Sclera in Response to Three Myopiagenic Conditions

Abstract: The very similar gene expression signatures produced in the sclera by the three different myopiagenic visual conditions at different time points suggests that there is a "scleral remodeling signature" in this mammal, closely related to primates. The scleral genes examined did not distinguish between the specific visual stimuli that initiate the signaling cascade that results in axial elongation and myopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 79 publications
6
57
0
Order By: Relevance
“…32 Downregulation of Col12a1 reported in our qRT-PCR data in both PPZ FD versus PPZ fellow eye and PPZ FD versus peripheral temporal FD fellow eye experiments is consistent with the above studies on matrix degradation observed during myopia. In the case of Timp3, upregulation was observed in both PPZ FD versus PPZ fellow eye and PPZ FD versus peripheral temporal FD fellow eye experiments, which is contrary to findings previously reported.…”
Section: Discussionsupporting
confidence: 92%
“…32 Downregulation of Col12a1 reported in our qRT-PCR data in both PPZ FD versus PPZ fellow eye and PPZ FD versus peripheral temporal FD fellow eye experiments is consistent with the above studies on matrix degradation observed during myopia. In the case of Timp3, upregulation was observed in both PPZ FD versus PPZ fellow eye and PPZ FD versus peripheral temporal FD fellow eye experiments, which is contrary to findings previously reported.…”
Section: Discussionsupporting
confidence: 92%
“…In response to myopiagenic visual stimuli, the retinal compartment of the direct emmetropization pathway generates GO signals that are conveyed into the RPE (He, Frost, & Norton, 2014), thence into the choroid (He et al, 2014), and eventually reach the sclera (Guo et al, 2013) where they modulate the axial elongation rate of the growing postnatal eye (Siegwart & Norton, 1998). It seems evident that the three GO conditions used in this study, minus lens wear, form deprivation, and continuous darkness, must produce dramatically different responses in many of the retinal horizontal, bipolar, and amacrine cells and in the patterns of retinal ganglion cell activity that are sent through the optic nerve to central visual structures, yet all three produce a nearly identical response in the scleral fibroblasts (Guo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that the retinal emmetropization-related signaling produced by these two GO conditions can be distinguished (Bartmann et al, 1994; Bitzer, Feldkaemper, & Schaeffel, 2000; Fujikado et al, 1997; Kee, Marzani, & Wallman, 2001; Schaeffel et al, 1994; Wildsoet, 2003; Yew & Wildsoet, 2003). However, in the sclera, it has been found that ML and FD produce nearly identical gene expression signatures; DK treatment also produces a similar gene expression signature (Guo et al, 2013). It appears that the different retinal activity produced by these three myopiagenic conditions may be converted into a common set of emmetropization signals as it passes through the direct RPE-choroid-sclera emmetropization pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The tree shrew is a small animal (a prosimian primate) indigenous to southwest Asia and has been used to study myopia and depression (21)(22)(23)(24). The recently published complete genome and transcriptome of the tree shrew suggest that it is closely related to primates (25,26).…”
mentioning
confidence: 99%